Impacts of gibberellin application on citrus: An overview from seed germination to fruit quality enhancement - Rahma, Siti Auliya; Budiarto, Rahmat; Mubarok, Syariful; Abdullakasim, Supatida (Universitas Padjadjaran, 2024)
Gibberellins are key plant hormones, and their application in citrus plants is frequently reported. This review aims to provide an overview of the application of gibberellic acid (GA3) in citrus cultivation, emphasizing their effects on growth, flowering, fruit quality, and ripening. Citrus fruits often face challenges like irregular fruit set, size inconsistency, and environmental stress, impacting yield and profitability, with exogenous gibberellin application as a potential solution. Applying gibberellins can accelerate citrus seed germination and seedling growth, enhance vegetative growth, inhibit flowering, delay fruit ripening, and improve fruit quality. However, the efficacy of gibberellins varies across species and conditions, highlighting the need for reference studies. This work presents an alternative option for optimizing gibberellin use to support sustainable citrus production practices.